Dosimetric study of uniform scanning proton therapy planning for prostate cancer patients with a metal hip prosthesis, and comparison with volumetric‐modulated arc therapy. (8th May 2014) - Rana, Suresh; Cheng, ChihYao; Zheng, Yuanshui; Hsi, Wen; Zeidan, Omar; Schreuder, Niek; Vargas, Carlos; Larson, Gary
Abstract : The main purposes of this study were to 1) investigate the dosimetric quality of uniform scanning proton therapy planning (USPT) for prostate cancer patients with a metal hip prosthesis, and 2) compare the dosimetric results of USPT with that of volumetric‐modulated arc therapy (VMAT). Proton plans for prostate cancer (four cases) were generated in XiO treatment planning system (TPS). The beam arrangement in each proton plan consisted of three fields (two oblique fields and one lateral or slightly angled field), and the proton beams passing through a metal hip prosthesis was avoided. Dose calculations in proton plans were performed using the pencil beam algorithm. From each proton plan, planning target volume (PTV) coverage value (i.e., relative volume of the PTV receiving the prescription dose of 79.2 CGE) was recorded. The VMAT prostate planning was done using two arcs in the Eclipse TPS utilizing 6 MV X‐rays, and beam entrance through metallic hip prosthesis was avoided. Dose computation in the VMAT plans was done using anisotropic analytical algorithm, and calculated VMAT plans were then normalized such that the PTV coverage in the VMAT plan was the same as in the proton plan of the corresponding case. The dose‐volume histograms of calculated treatment plans were used to evaluate the dosimetric quality of USPT and VMAT. In comparison to the proton plans, on average, the maximum and mean doses to the PTV were higher in the VMAT plans by 1.4% and 0.5%, respectively, whereas the minimum PTV dose was lower in the VMAT plans by 3.4%. The proton plans had lower (or better) average homogeneity index (HI) of 0.03 compared to the one for VMAT (HI = 0.04). The relative rectal volume exposed to radiation was lower in the proton plan, with an average absolute difference ranging from 0.1% to 32.6%. In contrast, using proton planning, the relative bladder volume exposed to radiation was higher at high‐dose region with an average absolute difference ranging from 0.4% to 0.8%, and lower at low‐ and medium‐dose regions with an average absolute difference ranging from 2.7% to 10.1%. The average mean dose to the rectum and bladder was lower in the proton plans by 45.1% and 22.0%, respectively, whereas the mean dose to femoral head was lower in VMAT plans by an average difference of 79.6%. In comparison to the VMAT, the proton planning produced lower equivalent uniform dose (EUD) for the rectum (43.7 CGE vs. 51.4 Gy) and higher EUD for the femoral head (16.7 CGE vs. 9.5 Gy), whereas both the VMAT and proton planning produced comparable EUDs for the prostate tumor (76.2 CGE vs. 76.8 Gy) and bladder (50.3 CGE vs. 51.1 Gy). The results presented in this study show that the combination of lateral and oblique fields in USPT planning could potentially provide dosimetric advantage over the VMAT for prostate cancer involving a metallic hip prosthesis. PACS number: 87.55.D‐, 87.55.ne, 87.55.dk